Stereotactic radiosurgery for treatment resistant depression: Systematic review - Jordan Vanleuven; Yusuke S. Hori; Tag Alsir Osama; Paul M. Harary; Austin Lui; Amit R. Persad; Armine Tayag; Sara C. Emrich; Louisa Ustrzynski; David Purger; David J. Park; Steven D. Chang (World Neurosurgery: X)
Background: Depression is a global health concern that significantly impacts the quality of life of those affected. Approximately 30 % of cases are resistant to currently approved treatment methods. This systematic review examines the state of research regarding radiotherapy, a non-invasive neurosurgical technique primarily used in cancer treatment, as a novel approach to treating treatment-resistant depression (TRD). Objective: To systematically review the literature on the use of stereotactic radiosurgery (SRS) for treating treatment-resistant depression. Methods: The PubMed, Embase, and Cochrane databases were searched using the terms “radiosurgery” AND (“depression” OR “treatment-resistant depression” OR “refractory depression”) and 994 results were identified. Inclusion criteria were studies using SRS as the sole means of treating depression or as the sole new treatment in previously refractory cases, regardless of sample size, length of follow-up, study design, participant characteristics, or experimental controls. Exclusion criteria included non-English studies, studies lacking primary data, and studies where improvements in depression were secondary to the improvement of another primary condition. Titles and abstracts were screened by two independent reviewers, and full texts of potentially eligible studies were assessed for eligibility. Results: Three studies met the inclusion criteria. All patients demonstrated significant amelioration of depressive symptoms following SRS, with sustained relief from depression observed over follow-up periods ranging from 1 to 5 years. No significant adverse effects were reported across the studies. Conclusions: Preliminary findings suggest that stereotactic radiosurgery may be a promising treatment option for TRD, offering a potentially safer, non-invasive alternative to current treatment methods. However, the small sample sizes and lack of randomized controlled trials underscore the need for further research to validate these findings.